Producing Early Modern London : A Comedy of Urban Space, 1598-1616 - Stage, Kelly J., 1978- (Book collections on Project MUSE., 2018)
"Producing Early Modern London analyzes theater's use of city spaces and places, showing how the satirical comedies of the early seventeenth century came to embody the city as the city embodied the plays"--